The carotid syndrome - Mori Chávez, P. (1935)
Since 1866 Czemark was observed that compression of the neurovascular bundle of the neck nerve causes marked bradycardia which he attributed to a direct stimulation of the vagus, has been referring to this concept a series of vegetative phenomena in medical and surgical diseases.